Changing Traditions: Supervision, Co-Teaching, and Lessons Learned in a Professional Development School Partnership - David S. Allen; Michael Perl; Lori Goodson; Twyla K. Sprouse (Educational Considerations, 2014)
Considering how long societies have been educating their youth, the history of teacher education is relatively brief. The first efforts to provide systematic education for teachers with some kind of practical experience occurred in Rheims, France, in the late 17th century when Jean Baptiste De La Salle opened the first normal school.
Keywords: traditional; supervision; observations triad model; teacher; supervisor; student; K-12 students; Co-teaching; Professional Development; partnership